Effect of BACE1-inhibited astrocytes on endothelial cells in a glutamate toxic environment (2020)
ABSTRACT: After cerebral ischemia or during several central nervous system (CNS) pathologies, exacerbated high glutamate concentration are released into the cerebral parenchyma producing a toxic environment that damages the components of the neurovascular unit (NVU) including the endothelial cells; which affects the function and structure of the blood-brain barrier. Astrocytes, glial cells that are closely related to the endothelium, change their gene expression profile in the face of toxicity and, depending of such profile, can be either protective or damage mediators. The enzyme BACE-1, involved in amyloidosis and vascular deterioration, increases its expression after an ischemic event even in astrocytes. Given the above, our aim was to determine the effect of BACE-1-inhibited astrocytes on endothelial cells integrity in a glutamate toxic environment by observing the effect of BACE-1 inhibition in endothelial cells and astrocytes cultures and endothelium-astrocyte co-cultures, through cytotoxicity and immunofluorescence assays. The results obtained suggest BACE1 inhibition protects endothelial cells integrity by reversing structural and inflammatory damage, also reverses astrocytic reactivity causing structural changes in cytoskeleton and cell inflammation. Furthermore, BACE1-inhibited astrocytes protect endothelial cells integrity regulating the Zonula occludens-1 distribution and decreasing inflammatory processes caused by glutamate toxicity. In summary, these results suggest inhibition of BACE1 under a glutamate toxicity has a protective effect on endothelium and astrocytes and their interactions.